A geospatial model of nature-based recreation for urban planning: Case study of Paris, France. (June 2022) - Liu, Hongxiao; Hamel, Perrine; Tardieu, Léa; Remme, Roy P.; Han, Baolong; Ren, Hai
Abstract: Incorporating nature-based recreation into urban planning analyses requires understanding the accessibility, quality, and demand for urban greenspace (UGS) across a city. Here, we present a novel tool that lowers the barriers to such information by (i) providing a spatially-explicit assessment of recreational UGS supply and demand; (ii) differentiating results by population group or UGS type; and (iii) using an accessible open-source software platform that facilitates scenario comparison and communication. In a case study in Paris, France, we demonstrate how the tool helps address important urban planning questions. We show that between 42% and 55% of the population is currently below the UGS target of 10 m 2 per person, depending on the accessibility criteria used. Using revealed preference data, we demonstrate that older adults are disproportionately affected by the UGS deficit. Our assessment of future scenarios reveals that UGS targets set by public policies are largely insufficient (500–2800 ha are planned by 2030, while more than 4000 ha are needed to meet the policy target). By combining the strengths of established geospatial methods, the tool helps researchers and practitioners produce a more nuanced analysis of the recreation benefits of UGS implementation. Highlights: A GIS tool quantifies the recreation service provided by urban greenspace (UGS). The tool accounts for different types of UGS (supply) and beneficiaries (demand). We demonstrate its application for urban planning in Paris, France. We identify population groups disproportionately affected by UGS deficit. The tool is open source and helps nuance assessments of urban recreation.